1977
DOI: 10.1107/s0021889877013958
|View full text |Cite
|
Sign up to set email alerts
|

A new automatic triple-crystal X-ray diffractometer for the precision measurement of intensity distribution of Bragg diffraction and Huang scattering

Abstract: A computer-controlled diffractometer has been built which permits intensity measurements to be made in any direction in reciprocal space in the diffraction plane with step sizes down to 0.01" of arc. Three examples illustrate the performance and application of the instrument: (a) perfect silicon, (b) gadolinium gallium garnet with growth striations and (c) niobium with low-angle grain boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Two peaks due to Ka I and Ko~ 2 components of the characteristic Ka line are well resolved owing to dispersion caused by different lattice spacings of the diffracting planes of the monochromator and the specimen crystals. The observed angular separation matches the theoretically expected value derived on this basis (Pick, Bickmann, Pofahl, Zwoll & Wenzl, 1977). Each of the peaks is quite sharp with a half-width of ,~11".…”
Section: Effect Of Film Deposition and Subsequent Annealing On Crystasupporting
confidence: 75%
“…Two peaks due to Ka I and Ko~ 2 components of the characteristic Ka line are well resolved owing to dispersion caused by different lattice spacings of the diffracting planes of the monochromator and the specimen crystals. The observed angular separation matches the theoretically expected value derived on this basis (Pick, Bickmann, Pofahl, Zwoll & Wenzl, 1977). Each of the peaks is quite sharp with a half-width of ,~11".…”
Section: Effect Of Film Deposition and Subsequent Annealing On Crystasupporting
confidence: 75%
“…Appropriate rotations of the sample and analyzer crystal allow undistorted and detailed maps to be recorded of reciprocal space in two or three dimensions and the effects arising from mosaicity to be deconvoluted from those due to other effects like planar defects and/or strain. The technique of RSM using the tripleaxis diffractometry and conventional X-rays has long been known (Pick et al, 1977). However, RSM more recently became a very powerful tool for the assessment of crystal perfection and investigations of structural inhomogeneities by the use of medium-or high-energy synchrotron X-rays.…”
Section: Assessment Of Crystal Quality and Reciprocal-space Mappingmentioning
confidence: 99%
“…The construction and testing of a simple double-crystal diffractometer has been described by Daenhardt (39), while Russian workers have reported on the construction of a 3-crystal device (87). The development of a computer controlled triple-crystal x-ray diffractometer by Pick et al (126) is clearly the most significant work reported in this field during the past two years. This device is able to automatically make intensity measurements in any direction in reciprocal space in the diffracting plane with step sizes down to 0.01 inch of arc.…”
Section: Instrumentationmentioning
confidence: 99%